A bee's eye view of remarkable floral colour patterns in the south-west Australian biodiversity hotspot revealed by false colour photography. (3rd July 2021) - Lunau, Klaus; Scaccabarozzi, Daniela; Willing, Larissa; Dixon, Kingsley
Abstract: Background and Aims: Colour pattern is a key cue of bee attraction selectively driving the appeal of pollinators. It comprises the main colour of the flower with extra fine patterns, indicating a reward focal point such as nectar, nectaries, pollen, stamens and floral guides. Such advertising of floral traits guides visitation by the insects, ensuring precision in pollen gathering and deposition. The study, focused in the Southwest Australian Floristic Region, aimed to spot bee colour patterns that are usual and unusual, missing, accomplished by mimicry of pollen and anthers, and overlapping between mimic-model species in floral mimicry cases. Methods: Floral colour patterns were examined by false colour photography in 55 flower species of multiple highly diverse natural plant communities in south-west Australia. False colour photography is a method to transform a UV photograph and a colour photograph into a false colour photograph based on the trichromatic vision of bees. This method is particularly effective for rapid screening of large numbers of flowers for the presence of fine-scale bee-sensitive structures and surface roughness that are not detectable using standard spectrophotometry. Key Results: Bee- and bird-pollinated flowers showed the expected but also some remarkable and unusual previously undetected floral colour pattern syndromes. Typical colour patterns include cases of pollen and flower mimicry and UV-absorbing targets. Among the atypical floral colour patterns are unusual white and UV-reflecting flowers of bee-pollinated plants, bicoloured floral guides, consistently occurring in Fabaceae spp., and flowers displaying a selective attractiveness to birds only. In the orchid genera ( Diuris and Thelymitra ) that employ floral mimicry of model species, we revealed a surprising mimicry phenomenon of anthers mimicked in turn by model species. Conclusion: The study demonstrates the applicability of 'bee view' colour imaging for deciphering pollinator cues in a biodiverse flora with potential to be applied to other eco regions. The technique provides an exciting opportunity for indexing floral traits on a biome scale to establish pollination drivers of ecological and evolutionary relevance.